PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR), KUALITAS MEREK DAN REPUTASI CSR TERHADAP PREFERENSI MEREK - Prastyo, Wahyu Langgeng; Pramudana, Km. Agus Satria (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the influence of Corporate Social Responsibility, CSR brand quality and reputation of the brand preference in the International Tbk PT.Astra-Honda in Denpasar. This research was conducted at the International Tbk PT.Astra-Honda in Denpasar. Data collection techniques used were interviews and questionnaires. The number of samples taken was 117 respondents using purposive sampling method. Data analysis technique used is the technique of multiple linear regression analysis. The analysis showed that the Corporate Social Responsibility positive and significant impact on brand preference. Quality brand positive and significant impact on brand preference. CSR reputation and positive and significant impact on brand preference. PT.Astra International Tbk-Honda in Denpasar should retain their products in order to reduce negative impacts on the environment posed, maintaining products using injection system and still maintain and increase a sense of concern for the surrounding communities.
Keywords: Brand Preferences, Corporate Social Responsibility Program, Brand Quality, Reputation CSR